Governmentality and counter-hegemony in Bangladesh - Alam, S. M. Shamsul, 1956- (New York : Palgrave Macmillan, 2015)
"Using Michel Foucault's idea of governmentality, this book reinterprets various cases of revolt and popular uprisings in Bangladesh. It attempts to synthesize the theories of Foucault's governmentality and Antonio Gramsci's notions of hegemony and counter-hegemony. Bangladesh's history of revolt and counter-hegemony are categorized as nationalist governmentality, authoritarian governmentality, and global/neo-liberal governmentality. Each of these phases, the author argues, is not a replacement or dislocation of the earlier governmentality in practice but rather a reformulation of the construct. This reconfiguration results from counter-hegemonic revolts launched by various subaltern categories. Throughout the book, the author asserts that governmentality and counter-conducts/counter-hegemonies are linked with and transformed by each other. Furthermore, by using Bangladesh as a case study, the author contemplates an idea of colonial and post-colonial governmentality"--
"By using Michel Foucault's idea of governmentality, this book reinterprets various cases of revolt and popular uprisings in Bangladesh. It attempts to synthesize the theories of Foucault's governmentality and Antonio Gramsci's notions of hegemony and counter-hegemony. In this book, Bangladesh's history of revolt and counter-hegemony are categorized as nationalist governmentality, authoritarian governmentality, and global/neo-liberal governmentality. Each of these phases, the author argues, is not a replacement or dislocation of the earlier governmentality in practice but rather a reformulation of the construct. This reconfiguration results from counter-hegemonic revolts launched by various subaltern categories. Throughout the book, the author asserts that governmentality and counter-conducts/counter-hegemonies are linked with and transformed by each other. Furthermore, by using Bangladesh as a case study, the author contemplates an idea of colonial and post-colonial governmentality"--
Machine generated contents note: -- Preface and acknowledgements -- 1. Introduction -- 2. Gorob O Asha: Language as Counter-Governmentality -- 3. Conscious Spontaneity: The Anti-Authoritarian Revolt of 1968-69 -- 4. Nationalism as (Re) Governmentalization -- 5. Military Authoritarian Governmentality and Its Displacement -- 6. Islamic Governmentality? The Taslima Nasrin Case -- 7. Ethnicization and (Counter) Governmentality in the Chittagong Hill Tracts -- 8. On Rape and Revolt -- 9. Global (Counter) Governmentality -- 10. Coda: Governance without Governmentality? -- Notes -- Bibliography -- Index -- About the Author.
Includes index.
Bibliography: p. 197-215.
Keywords: Power (Social sciences) -- Bangladesh; Bangladesh -- Politics and government -- 1971-